Multiplexed Microneedle-based Biosensor Array for Characterization of Metabolic Acidosis - Miller, Philip R. (2011)
The development of a microneedle-based biosensor array for multiplexed in situ detection of exercise-induced metabolic acidosis, tumor microenvironment, and other variations in tissue chemistry is described. Simultaneous and selective amperometric detection of pH, glucose, and lactate over a range of physiologically-relevant concentrations in complex media is demonstrated. Furthermore, materials modified with a cell-resistant (Lipidure®) coating were shown to inhibit macrophage adhesion; no signs of coating delamination were noted over a 48-hour period.